Rehabilitation for cognitive impairments after cerebral malaria in African children: strategies and limitations - Bangirana, Paul; Idro, Richard; John, Chandy C.; Boivin, Michael J. (Tropical Medicine & International Health, 2006)
Cerebral malaria results in short- to long-term cognitive impairments in many of its child survivors. Although some of the risk factors for impairments have been identified, no attempts have been made to address the plight of those who develop cognitive impairments. This paper discusses the burden of cognitive impairment caused by cerebral malaria and suggests some rehabilitation strategies based on brain injury and cognitive rehabilitation studies. Potential cognitive rehabilitation solutions such as cognitive exercises, environmental enrichment, nutritional supplementation, physical therapy and speech therapy are highlighted. The limitations of implementing these interventions and solutions are discussed in light of the limited human resources and infrastructure of the developing countries that are malaria endemic.
Keywords: Cerebral malaria, cognitive impairment, Africa, children, rehabilitation Introduction Malaria is a leading cause of ill health in tropical countries. About 515 million clinical episodes were estimated to have occurred in 2002; 70% in Africa and 25% in South East Asia and was responsible for about one million deaths in children under 5 years of age in sub-Saharan Africa (Snow et al. 2005). Most of the malaria-related deaths result from the severe forms of falciparum malaria. Cerebral malaria (CM) is the most severe neurological complication of falciparum malaria. Despite adequate medical care, mortality stands at 18.6% and 10.9% of survivors are discharged with gross neurological deficits (Newton et al. 2000). Because of this high mortality, little attention has been paid to the long-term outcomes of the disease. However, recent studies have shown that neurologic and cognitive deficits may persist in many survivors of CM. This paper examines the cognitive deficits that follow recovery from CM and outlines strategies that may help in rehabilitation. A meta-analysis on studies looking at the cognitive impairments in